ETIKA DAN KODE ETIK PROFESI HUKUM - Sidharta, B. Arief (Faculty of Law, Parahyangan Catholic University, 2015)
AbstractOne of the most important aspects of society is a well functioning professionals scientifical development and application are carried out by professionals and modern society cannot exit without both. The same can be said in regard to the legal profession, in this paper represented by judges and advocates. Profession therefore should be regarded an institutional framework, in which the development and teaching of sciences and humanities and its practical application in the field of spiritual service, medicine, technology, law, information and education are to be realized. Practice howerver tell a different story, and professionals perform their work within a certain socio-political field. This paper discusses the inter-relationship between professionals and their respective ethical rights and duties.